An Assessment of the Contributions of Ecosystem Services in Guinea-Bissau: A Case Study of Cantanhez National Park: Analise da contribuição dos serviços ecossistêmicos na Guiné-Bissau: Caso de estudo Parque nacional de Cantanhez - Fernandes, Joaquim Silva; Foye, Victoria Oluwatoyin; Cardoso, Leonildo Alves (Sociedade & Natureza, 2025)
Valuation of ecosystem services (ES) is vital for national growth and development, particularly in Guinea-Bissau which is ranked among the poorest nations worldwide. Therefore, this study assessed the contributions of five ES (land, sea, medicinal plant, mangrove and tourism) in the Cantanhez National Park with a view to establishing their effects on the growth and development of Guinea-Bissau. Data were purposively obtained through semi-directed interviews and questionnaires from 226 respondents in Tombali. A multi-stage sampling method was employed in this study. At the primary stage, the purposive sampling technique was used to select 11 villages closely situated 3-4km apart within Cantanhez Park while at the secondary stage, a second stage of purposive sampling was employed in the selection of 20 individuals in each village and at the final stage, face-to-face interviews were conducted to establish the robustness of our results. The study adopted the Contingent Valuation Method to elicit information from respondents, while data were subjected to descriptive statistics. The study revealed that people were willing to pay between 1 and 25000 FCFA for the ES, an average of about 12,500 FCFA based on the income of respondents. This value was used to project the additional income and per capita income that could be generated annually from the five ES. These were approximately 5.07 billion FCFA and 2574.09 FCFA respectively. The result showed that ES observed in this study could contribute to the growth and development of Guinea Bissau; and to ensure maximal contribution, successful implementation of the conservatory and regulatory policies is requisite. The study concludes that periodic ecological valuation of ES is essential for inclusive growth and sustainable development.